A Practical Approach to Teaching eBusiness System Concepts - March, Salvatore T. (Senate Hall Academic Publishing, 2004)
Introductory courses in Electronic Business (eBusiness) must emphasize end-to-end integration of information flows from the marketing of products and services and the acquisition of customer orders through fulfillment, production, and supply chain management. A tutorial uses Microsoft FrontPage, a Microsoft Access database, and a set of utility Active Server Page (ASP) programs to demonstrate how these capabilities are implemented. In a series of five assignments students develop a Web system focusing on customer registration, order acquisition, payment, and order tracking. An Intranet site is provided to illustrate the fulfillment processes. This paper discusses these components and how they are used to illustrate and demonstrate important eBusiness concepts. A server environment utilizing Microsoft FrontPage Server Extensions enables each student to remotely create their Web system with its own database. Process visibility is supported through point and click database accessibility. Overall student time to create the system is seven to eight hours, approximately one and one half hours per assignment. All tutorial materials and assignments are available at http://SalMarch.com/eB.
Keywords: e-business technology; web storefront; e-sales order processing; e-fulfillment; backend-integration